Islamic Financial Inclusion as a Transmission Channel: Evidence from Digital Payments and Inflation in Indonesia - Pribawa E Pantas; Norfaizah Othman; Noor Aimi Mohamad Puad (Al-Tijary, 2026)
This study investigates the role of Islamic financial inclusion as a transmission channel linking digital payments and inflation in Indonesia's dual banking system. While digital payment systems have expanded rapidly and are known to influence monetary policy transmission, the mechanism through which these effects occur—particularly within an Islamic finance context—remains underexplored. Using monthly data from January 2016 to June 2025, this study employs an Autoregressive Distributed Lag (ARDL) model combined with a mediation framework to examine both direct and indirect effects. The findings reveal that digital payments significantly enhance Islamic financial inclusion, thereby influencing inflation dynamics through an indirect transmission mechanism. Mediation analysis confirms that Islamic financial inclusion partially transmits the impact of digital payments to inflation, with the indirect effect accounting for approximately 15.5% of the total effect. These results contribute to the literature by integrating Islamic finance into macroeconomic transmission analysis and provide policy implications for strengthening inclusive, sharia-compliant financial ecosystems in emerging economies.